Проблемы становления и развития украинского этноса в свете дискурса Л. Н. Гумилёва с представителями украинской исторической мысли - Лепинская, В.О. (Культура народов Причерноморья, 2013)
В статье рассматривается история становления и развития украинского этноса в свете
концепций и трудов украинских исследователей, а также делается попытка выявить схожесть и
различия отдельных положений доктрин украинских учёных относительно развития украинского
этноса с теорией Л.Н. Гумилёва, в которой сделан акцент на таких основных составляющих этноса
как: ландшафт, стереотип поведения и пассионарность. Эти понятия можно проследить у учёных,
которые исследовали украинскую историю. У статті розглядається історія становлення та розвитку українського етносу в світлі
концепцій і праць українських дослідників, а також робиться спроба виявити схожість і відмінності
окремих положень доктрин українських вчених щодо розвитку українського етносу з теорією
Л.М. Гумільова, в якій зроблено акцент на таких основних складових етносу як: ландшафт, стереотип
поведінки і пасіонарність. Ці поняття можна простежити у вчених, які досліджували українську
історію. The article discusses the history of formation and development of the Ukrainian nation in the light of
the concepts and works of Ukrainian researchers, as well as attempts to identify similarities and differences of
certain provisions of the doctrines of Ukrainian scientists on the development of the Ukrainian nation with the
theory L.N. Gumilev, which focuses on the core components of ethnic group as landscape pattern of behavior
and passionateness. These concepts can be traced to the scientists who studied Ukrainian history.
The article discusses the works of Ukrainian scientists devoted to the history and formation of the Ukrainian
nation, similar provisions found in the concepts of Ukrainian researchers with the theory of ethnogenesis
L.N. Gumilev, formed the methodology for determining the principles of formation of the Ukrainian nation.
Interest in the origin of the Ukrainian nation and its predecessor the Slavic emerged among researchers for a
long time. First of all, scientists have drawn attention to the questions of the origin of the Slavs, Kievan Rus, the
Ukrainian nation, especially the customs and manners of the people, government organizations, as well as
natural and geographical environment. Concept L.N. Gumilev unites all these provisions, which gives an
opportunity to form a holistic, systematic approach to the events that are happening now, to establish a causal
link with the past and create a methodology to determine the principles of formation of the Ukrainian nation.